STUDI KEBIJAKAN PROGRAM MAKANAN TAMBAHAN BISKUIT PADA BALITA KURANG GIZI DI KOTA SOLOK TAHUN 2020 - Esinelya Esinelya; Masrul Masrul; Firdawati Firdawati (Universitas Fort De Kock, 2021)
ABSTRACTOne of the policies of the Ministry of Health in preventing and overcoming nutritional problems in children under five is the supplementary feeding program. This program has been started since 1998, however, the success rate in reducing the prevalence of nutritional problems has not been as expected. To find out the implementation of the biscuit complementary food program and its problems, researchers conducted the research in Solok city. This research conduct by mixed methods. The informants were the Head of the Health Office, the Head of the Nutrition Kesga Section, the Nutrition Program Manager, the Head of primery health centre, the Nutritionist, the Pustu/Poskeskel supervisors and the Toddler Mother. Measurement of body weight of toddlers can additional food program is done to determine the average weight gain per month. Results: input, the policy of the biscuit additional food program, which refers to the technical guidelines. Fund utilization has not been optimal. Human resources, inadequate quality. The biscuit storage space is not fulfill the standard. Availability of target characteristics is incomplete. The process is that there is no SOP and POA, the target biscuit recipients have not referred to the technical instructions, the taking of biscuits is irregular, the understanding of mothers about program, nutrition education, recording/reporting, monitoring evaluation are not optimal. Output, 67,4% of toddlers are unable to finish biscuits because they do not like it, bored and consumed by other family members. Output 41,2% of children under five have gained weight less than KBM. It is suggested that the public health office be able to motivate to understanding to mother about the purpose and objectives of providing biscuit and improve the quality of nutrition services guided by toddler nutrition care Keywords : Malnourished toddlers, Biscuit additional food ABSTRAKSalah satu kebijakan Kementerian Kesehatan dalam mencegah dan menanggulangi masalah gizi balita adalah program pemberian makanan tambahan sejak tahun 1998, namun tingkat keberhasilannya dalam menurunkan prevalensi masalah gizi belum sesuai harapan. Untuk mengetahui pelaksanaan program makanan tambahan biskuit dan permasalahannya, peneliti melakukan penelitian di kota Solok. Penelitian menggunakan metode studi kebijakan. Informan Kepala Dinas Kesehatan, Kasi Kesga Gizi, pengelola program gizi, Kepala Puskesmas, Tenaga Gizi Puskesmas, petugas Pustu/Poskeskel dan ibu balita. Pengukuran berat badan balita dapat MT biskuit dilakukan untuk mengetahui kenaikan berat badan rata-rata per bulan. Hasil Penelitian : input, kebijakan pelaksanaan program MT biskuit mengacu pada petunjuk teknis. Pemanfaatan dana belum optimal. SDM sebagian kualitasnya kurang, penyimpanan biskuit belum sesuai standar. Ketersediaan karakteristik sasaran belum lengkap. Proses, belum tersedia SOP dan POA, sasaran dapat biskuit belum mengacu pada petunjuk teknis, ketidakteraturan pengambilan biskuit, pemahaman ibu tentang program, edukasi gizi, pencatatan/pelaporan dan monev belum optimal. Output, 64,7% balita tidak mampu menghabiskan biskuit karena tidak suka, bosan dan dikonsumsi oleh anggota keluarga lain. 41,2% balita mengalami kenaikan berat badan < KBM. Disarankan dinas kesehatan dapat motivasi dan memberi pemahaman lebih dalam pada ibu tentang maksud/ tujuan pemberian MT biskuit sehingga biskuit dapat dikonsumsi sesuai anjuran serta meningkatkan kualitas pelayanan gizi dengan berpedoman pada Asuhan Gizi Balita. Kata Kunci : Balita Kurang Gizi, Makanan Tambahan Biskuit